Trends and determinants of pregnancy loss in eastern Ethiopia from 2008 to 2019: analysis of health and demographic surveillance data - Lemma Demissie Regassa; Assefa Tola; Gamachis Daraje; Merga Dheresa (BMC, 2022)
Abstract Background Pregnancy losses remain a neglected issue and it will be taking more than a century before a pregnant woman in Sub Sahara has the same chance of her baby being born alive as a woman in a high-income country. Pregnancy loss data are limited and not universal in Sub Saharan countries. This study was aimed to assess the magnitude and determinants of pregnancy loss in eastern Ethiopia. Methods This study was conducted in, open continues and dynamic cohort of population, Kersa Health and Demographic Survillance site (HDSS) in Eastern Ethiopia in 2008-2019. All mothers who had known pregnancy outcomes during the period and reside in Kersa HDSS were considered. The prevalence proportions were calculated as the sum of all pregnancy loss divided by the number births in the specified year. Log-Binomial regression was used to determine factors associated with pregnancy loss. Prevalence Proportion Ratio (PPR) was used to report the magnitude and strength of association. A p-value of less than 0.05 was considered statistically significant. Results From 39,153 included pregnancies, 810 (20.7; 95%CI:19.32, 22.15 per 1000 births) experienced pregnancy loss. Stillbirth was higher than abortion (11.14 Vs. 9.55 per 1000 births). Lacking own income (aPPR:1.26; 95%CI: 1.01, 1.58), being daily laborer (aPPR:1.44; 95%:1.08, 306) history of previous pregnancy loss (aPPR:2.26, 95%CI:1.69, 3.03), unwanted pregnancy (aPPR:1.26; 95%CI:1.01, 1.80), not receiving antenatal care (aPPR:1.59; 95%CI: 1.19, 2.13) and not receive the TT-vaccine during pregnancy (aPPR:1.33; 95%CI: 1.08, 1.80) were positively associated with pregnancy loss. Conclusions The overall rate pregnancy loss was ranged between 19.32, 22.15 per 1000 births with higher still births than miscarriage or abortion. Pregnancy loss was positively associated with social factors reproductive health factors, and maternal health service utilization.